2018
DOI: 10.2459/jcm.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in heart failure

Abstract: Due to aging of the patients with heart failure, comorbidities are an emerging problem and, among them, iron deficiency is an important therapeutic target, independently of concomitant hemoglobin level. Iron deficiency affects up to 50% of heart failure patients, and it has been largely established its association with poor quality of life, impaired exercise tolerance and higher mortality. Randomized controlled trials (RCTs) and meta-analyses have demonstrated that intravenous iron supplementation in heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
0
6
1
1
Order By: Relevance
“…The reason for the influence of haemoglobin on mortality has to be sought in the reduced oxygen-carrying capacity of blood that brings to increased cardiac work, elevated demand-related ischaemia, and renal hypoxia. 37 Moreover, our multivariable analysis did not point high non-sensitive TnI levels and hyponatremia as independent predictors of mortality, in contrast to several studies. [38][39][40][41][42][43] Finally, we found that an EF <40% was the only predictor of both all-cause mortality and CV mortality at the multivariable analysis.…”
Section: Predictors Of Outcomescontrasting
confidence: 98%
“…The reason for the influence of haemoglobin on mortality has to be sought in the reduced oxygen-carrying capacity of blood that brings to increased cardiac work, elevated demand-related ischaemia, and renal hypoxia. 37 Moreover, our multivariable analysis did not point high non-sensitive TnI levels and hyponatremia as independent predictors of mortality, in contrast to several studies. [38][39][40][41][42][43] Finally, we found that an EF <40% was the only predictor of both all-cause mortality and CV mortality at the multivariable analysis.…”
Section: Predictors Of Outcomescontrasting
confidence: 98%
“…However, in a recent analysis of the MECKI score database 27 performed in 3927 HFrEF patients, a worse prognosis was observed in patients with poor glycaemic control (HbA1c >8%) (Figure 1), whereas the presence of a diabetic status and ongoing anti-diabetic treatment were not related to prognosis after correction for multiple confounders. 8 Left ventricular (LV) dysfunction in patients with type 2 diabetes may present as HFpEF, HFrEF or heart failure with mid-range ejection fraction. LV diastolic dysfunction is frequent in both pre-diabetes and overt diabetes, and its severity correlates with insulin resistance and the degree of glucose dysregulation.…”
Section: Diabetesmentioning
confidence: 99%
“…7 As already discussed for anaemia, also iron deficiency, alone or combined with an anaemic status, is responsible for reduced exercise tolerance, affects quality of life and results in higher rates of hospitalizations and death in heart failure patients. 8 As regards exercise intolerance, Jankowska et al. 9 reported in 443 chronic heart failure patients the independent role of iron deficiency in determining reduced exercise capacity.…”
Section: Anaemia and Iron Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Iron deficiency affects up to 50% of heart failure patients and has been associated with poor quality of life, impaired exercise tolerance, and increased mortality [7]. The case presented here shows that intravenous iron supplementation not only rendered the patient operable with respect to his recently detected colon carcinoma, but also effectively improved the cardiac symptoms he had been assessed for in the first place.…”
Section: Discussionmentioning
confidence: 78%